2022
DOI: 10.1523/eneuro.0373-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Imaging Cranial Sensory Ganglion Neurons Using AAV-PHP.S

Abstract: Because of their ease of use, adeno-associated viruses (AAVs) are indispensable tools for much of neuroscience. Yet AAVs have been used relatively little to study the identities and connectivity of peripheral sensory neurons, principally because methods to selectively target peripheral neurons have been limited. The introduction of the AAV-PHP.S capsid with enhanced tropism for peripheral neurons ( Chan et al., 2017 ) offered a solution, which we further elaborate here. Using AAV-PHP.S w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Simultaneously, the glossopharyngeal nerve, which innervates the taste buds of the foliate papillae and circumvallate papillae in the posterior tongue, possesses cell bodies in the petrosal ganglion. By expressing a GCaMP variant with transgenic mice ( Fowler and Macpherson, 2021 , Fowler et al, 2022 , Wu et al, 2015 ) or AAV vector ( Asencor et al, 2022 , Lee et al, 2017 ), the calcium activity in ganglion neurons was measured upon oral exposure to various tastants. Most ganglion neurons exhibit a narrow spectrum of profiles in response to specific modalities ( Fowler et al, 2022 , Lee et al, 2017 , Wu et al, 2015 ).…”
Section: Ganglionmentioning
confidence: 99%
“…Simultaneously, the glossopharyngeal nerve, which innervates the taste buds of the foliate papillae and circumvallate papillae in the posterior tongue, possesses cell bodies in the petrosal ganglion. By expressing a GCaMP variant with transgenic mice ( Fowler and Macpherson, 2021 , Fowler et al, 2022 , Wu et al, 2015 ) or AAV vector ( Asencor et al, 2022 , Lee et al, 2017 ), the calcium activity in ganglion neurons was measured upon oral exposure to various tastants. Most ganglion neurons exhibit a narrow spectrum of profiles in response to specific modalities ( Fowler et al, 2022 , Lee et al, 2017 , Wu et al, 2015 ).…”
Section: Ganglionmentioning
confidence: 99%
“…Chan et al used a technique they named CREATE (Cre recombinase-based AAV targeted evolution) to select capsids specific to different cell types, which gave rise to AAV-PHP.eB and AAV-PHP.S, which effectively transduced the central and peripheral nervous systems, respectively. 45 Based on these findings, Asencor et al systematically investigated and reported the neuroanatomical tracing results of AAV-PHP.S in peripheral nerves like the geniculate nerve (cranial nerves V, VII, IX, and X), illuminating for the first time the sensory properties of auricular neurons in the geniculate ganglion 46 [Fig. 3A].…”
Section: Axonal-related Tracers or Antibodiesmentioning
confidence: 99%
“…By introducing particular peptides into the heparin-binding loop, Gowanlock et al created the retrograde tracer rAAV2-retro, which could be efficiently retrograde delivered to projection neurons in the mouse brain. 44 With its effective retrograde transport and 45 Based on these findings, Asencor et al systematically investigated and reported the neuroanatomical tracing results of AAV-PHP.S in peripheral nerves like the geniculate nerve (cranial nerves V, VII, IX, and X), illuminating for the first time the sensory properties of auricular neurons in the geniculate ganglion 46 [Fig. 3A].…”
Section: Axonal Transport-based Neuroanatomical Tracersmentioning
confidence: 99%